Analysis of risk factors for the failure of respiratory support with high-flow nasal cannula oxygen therapy in children with acute respiratory dysfunction: A case–control study - Liu, Jie; Li, Deyuan; Luo, Lili; Liu, Zhongqiang; Li, Xiaoqing; Qiao, Lina (Frontiers in Pediatrics, 2022)
Evidence-based clinical practice guidelines regarding high-flow nasal cannula(HFNC) use for respiratory support in critically ill children are lacking.Therefore,we aimed to determine the risk factors for early HFNC failure to reduce the failure rate and prevent adverse consequences of HFNC failure in children with acute respiratory dysfunction.Demographic and laboratory data were compared among patients,admitted to the pediatric intensive care unit between January 2017 and December 2018, who were included in a retrospective cohort study.Univariate and multivariate analyses were performed to determine risk factors for eventual entry into the predictive model for early HFNC failure and to perform an external validation study in a prospective observational cohort study from January to February, 2019.Further, the association of clinical indices and trends pre- and post-treatment with HFNC treatment success or failure in these patients was dynamically observed.In total,348 pediatric patients were included,of these 282(81.0%) were included in the retrospective cohort study;HFNC success was observed in 182 patients(64.5%),HFNC 0–24h failure in 74 patients(26.2%), and HFNC 24–48h failure in 26 patients(9.2%). HFNC 24h failure was significantly associated with the PRISM III score, PaCO2/PaO2 ratio,and ROX index.The discriminating cutoff point for the new scoring system based on the three risk factors for HFNC 24h failure was≥2.0 points, with an area under the receiver operating characteristic curve of 0.794(95% CI,0.729–0.859,P<0.001), sensitivity of 68%, and specificity of 79%;similar values were noted on applying the model to the prospective observational cohort comprising 66 patients.In this prospective cohort, 11 patients with HFNC failure had an upward trend in PaCO2/PaO2 ratio and downward trends in P/F ratio and ROX index;however,opposite directions of change were observed in 55 patients with HFNC success.Furthermore,the fractional changes in PaCO2/PaO2 ratio, P/F ratio, S/F ratio, and ROX index at 2h post-HFNC therapy onset were statistically significant between the two groups.In the pediatric patients with acute respiratory insufficiency,pre-treatment PRISM III score,PaCO2/PaO2 ratio,and ROX index were risk factors for HFNC 24h failure,and the direction and magnitude of changes in the PaCO2/PaO2 ratio,P/F ratio,and ROX index before and 2h after HFNC treatment were warning indicators for HFNC 24h failure. Further close monitoring should be considered for patients with these conditions.